2009
DOI: 10.1080/00103620903221225
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Continuous Rice–Wheat Rotation on Soil Properties from Four Agro‐ecosystems of Indian Punjab

Abstract: In Indian Punjab, rice-wheat is a dominant cropping system in four agro-ecosystems, namely undulating subregion (zone 1), Piedmont alluvial plains (zone 2), central alluvial plains (zone 3), and southwestern alluvial plains (zone 4), varying in rainfall and temperature. Static and temporal variabilities in soil physical and chemical properties prevail because of alluvial parent material, management/tillage operations, and duration of rice-wheat rotation. A detailed survey was undertaken to study the long-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 16 publications
5
15
0
Order By: Relevance
“…The lower OC content in the lower layers during 2008 may be blocking of translocation of organic matter due to the formation of impervious layer below the surface having higher bulk density (1.8 g cm 3 ). Similar results were also reported by other studies [23][24][25][26] . Decreasing trend in pH was observed in the surface soils (7.3 Soils occurring on recent flood plain are not fully developed.…”
supporting
confidence: 80%
“…The lower OC content in the lower layers during 2008 may be blocking of translocation of organic matter due to the formation of impervious layer below the surface having higher bulk density (1.8 g cm 3 ). Similar results were also reported by other studies [23][24][25][26] . Decreasing trend in pH was observed in the surface soils (7.3 Soils occurring on recent flood plain are not fully developed.…”
supporting
confidence: 80%
“…Water retained by different soils at varying suctions in the four agro climatic zones of Punjab where puddling has been continuous from more than 15 years is reported by Singh et al (2009). Water retention was higher in zone 1(undulating sub region), followed by zone 2 (piedmont alluvial plains) and zone 3 (central alluvial plains) and least in zone 4 (southwestern alluvial plains) ( Figure 1a).…”
Section: Climate Texture and Soil Depthmentioning
confidence: 80%
“…Amongst the textural class, saturated hydraulic conductivity was significantly more in sandy clay loam due to more sand content in the soil (66 per cent) than other classes, where it ranged from 31-55 per cent. Saturated hydraulic conductivity was more in the surface soil (due to more organic carbon and less bulk density) and it decreased with depth and was lowest in 15-22.5 cm soil layer, where bulk density and organic carbon were having reverse trend than the surface soil (Singh et al, 2009 Table 2. Averaged effects of agro climatic zones, textures and soil depths on saturated hydraulic conductivity.…”
Section: Climatementioning
confidence: 99%
See 1 more Smart Citation
“…Studies in Punjab (Kukal and Aggarwal, 2003;and Singh et al, 2009) have shown the presence of a high soil bulk density (ρ b ) layer at 15-25 cm soil depth under this monoculture. Therefore, there is a need to diversify the prevailing wheat-rice cropping system with the wheat-maize system, which will help in preventing the deterioration of soil health as well as restricting the fall of underground water by consuming less water as compared to rice.…”
Section: Introductionmentioning
confidence: 99%